Comparative assessment of respiratory, hematological and inflammatory profiles of long-term users of cigarettes, shisha, and e-cigarettes in Saudi Arabia - Mazen M. Homoud; Rowaida Qoutah; Gokul Krishna; Noran Harbli; Layan Saaty; Afrah Obaidan; Abdulrahman Alkhathami; Noran Jamil; Tala Μ. Alkayyat; Maryam Alsughayyir; Nada Gubari; Saleh Alkhathami; et al. (Tobacco Induced Diseases, 2025)
Introduction Globally, over 1 billion people smoke, resulting in approximately 8 million deaths each year. Although the health risks associated with traditional cigarettes are extensively documented, there is an increasing need to evaluate the long-term effects of alternative tobacco products, particularly shisha, and e-cigarettes. This study seeks to compare the respiratory, hematological, and inflammatory profiles of long-term users of cigarettes, shisha, and e-cigarettes in Saudi Arabia.